Multiple period resonances in long period gratings in photonic crystal fibres - Kalli, Kyriacos; Petrovic, Jovana S.; Mezentsev, Vladimir K.; Dobb, Helen L.; Webb, David; Bennion, Ian (My University, 2006)
In order to characterise long period gratings fabricated in endlessly single mode photonic crystal fibres with bulk cladding we perform eigenanalysis of guided modes supported by these fibres. Resonant coupling occurs only when the beating length equals the multiple grating periods. Experimentally obtained grating spectra and sensitivity are fully explained using modified phase matching condition.
Keywords: Photonic crystals; Fibers; Crystals; Optical fibers